Diagnosing Desire Biopolitics and Femininity into the Twenty-First Century - Spurgas, Alyson K. (The Ohio State University Press, 2020)
In Diagnosing Desire: Biopolitics and Femininity into the Twenty-First Century, Alyson K. Spurgas examines the "new science of female sexuality" from a critical, sociological perspective, considering how today's feminist-identified sex researchers study and manage women with low desire. Diagnosing Desire investigates experimental sex research that measures the disconnect between subjective and genital female arousal, contemporary psychiatric diagnoses for low female desire, new models for understanding women's sexual response, and cutting-edge treatments for low desire in women-including from the realms of mindfulness and alternative healing.